The Relevance of Imam Al-Ghazali's Akhlaki Sufism Method to the Goals of Islamic Religious Education - Suseno, Suseno; Syahrir, Sultan; Gani, Ainal (Universitas Sang Bumi Ruwa Jurai, 2025)
Islamic religious education plays a vital role in shaping students’ moral, spiritual, and emotional character. One relevant approach to achieving this goal is the akhlaki sufism method taught by Imam Al-Ghazali. This study aims to identify and analyze Imam Al-Ghazali’s akhlaki sufism method, the objectives of Islamic education, and the relevance between the two. This method emphasizes seven traits or practices that help students understand the importance of repentance, patience, refraining from criticizing poverty, living in asceticism (zuhud), placing full trust in Allah, loving Allah more than other beings, and accepting destiny with contentment. The research employed a descriptive-analytical method. The collected data were analyzed to identify akhlaki sufism concepts that can be integrated into the Islamic religious education curriculum and how these concepts can contribute to students’ character development. The findings reveal that Imam Al-Ghazali’s akhlaki sufism method consists of seven essential traits or practices which include repentance, patience, refraining from criticizing poverty, living in asceticism, trusting Allah, loving Allah above all else, and accepting destiny with contentment. This method is relevant to Islamic religious education in fostering students’ moral, spiritual, and emotional strength.